Comparative Performance of Water User Associations Policy: a Showed Case of Gezira Scheme, Sudan - M. Ahmed, Shamseddin; E. Bashier, Eltigsini; M. Adeeb, Ali (Gezira Journal of Engineering and Applied Sciences, 2013)
Gezira  scheme (0.88 million  hectare) has  recently  showed  a low  level   of  economical   efficiency. The government  introduced the  policy  or  water  users'  associations  (WLJAs)  in  2005  to  be responsible   for   water.  management    and    crop    choices.  The objective   of   this   study   is   to   the   performance  of WUAs   in Gezira  Scheme  using  selected  remotely sensed -  based  indicators. Images  were  collected  for  three   seasons  2004/2005, 2005/2006 and  2011/2012,  representing  the  period  prior  to  the  WUA,  the start  season  of   the  policy  and  a validation  season, respectively. Based  on  the  Mann - kendall  test  the  cultivated  area  showed a significant  decreasing  trend  (P = 0.002) for  the  last  thirty  years with   a current   cropping   intensity  of   0.48. The   study  showed mixed    results,  The  adoption  of   WUAs   policy   resulted  in  no significant    improvement   (P = 0.29)   in    the    monthly   overall consumed   ratio,  indicating   the   poor   performance   of   WUAs policy.   The  scheme  water  depletion  fraction  (DE) was found poor (less    than  1%)    throughout    the    studied    seasons  due   to   high evaporation    losses.  Relatively,   the   adoption  of    WUAs   policy however  in  the  second  season  is  significantly  increased (P = 0.0) the   DF   from   0.07%    to    0. I %   because  of  the improvement in irrigation   adequacy,  This   improvement   was  not   sustained  since the   DF   was   decreased   to   0.05%  in the validation season. On the basis   of   standardized   gross   value   of   production,    the   WUAs policy   succeeded   ill   increasing   fanners'   income by widened crop choices.  The  WUAs   policy   is   a good  turning point; however  its adoption  should  be  followed  by  irrigation  canal  maintenance  and capacity building programs.